Relationship between single-nucleotide polymorphisms and cancer immunotherapy efficacy and toxicity: a systematic review - Specchia, Monia; Siringo, Marco; Mazzotti, Eva; Mazzuca, Federica (Frontiers in Oncology, 2025)
Immunotherapy has revolutionized cancer treatment by using the body’s immune system to target and eliminate tumor cells. Immune checkpoint inhibitors (ICIs), such as anti-PD-1/PD-L1 and anti-CTLA-4 therapies, have shown substantial clinical benefits in many types of cancer. Despite their efficacy, not all patients benefit from them, and there is a need to identify biomarkers to predict responses and adverse events. This systematic review explores the role of single nucleotide polymorphisms (SNPs) in cancer immunotherapy, focusing on genes involved in immune checkpoint regulation. A comprehensive literature search was conducted across two databases, PubMed and Cochrane, published from 2000 to 2024, for a total of 884 works. The final analysis included 29 records that assessed the impact of SNPs on immunotherapy responses and toxicities. Findings suggest that specific SNPs in the CTLA-4, PD-1, and PD-L1 genes influence both treatment outcomes and the risk of immune-related adverse events across various cancers. For instance, certain CTLA-4 and PD-1 SNPs were associated with better survival rates or higher toxicity risks, while PD-L1 SNPs influenced tumor responses to ICIs. Specific SNPs, such as those in the CTLA-4 and PD-1 genes, have been linked to improved survival or increased toxicity risk. Additionally, PD-L1 SNPs can impact tumor response to ICIs, offering insights into their potential as predictive biomarkers. The findings emphasize the importance of SNPs in personalized cancer therapy, enabling more effective and safer treatment strategies. However, further research is needed to validate these genetic markers and optimize their clinical utility in immunotherapy.